Assessing the Nepalese Economy Through the Vision of Cooperative Resources - Kharel, Khom Raj; Upadhyaya, Yadav Mani; Khadka, Ramesh Bahadur (Janapriya Journal of Interdisciplinary Studies, 2022)
This article examines cooperative development strategies and resource mobilization to analyze Nepal’s cooperative development. Analytic approaches were used to explore the design and regulations of the coop in new developments, and resource mobilization was investigated using simple statistical tools. The study’s primary purpose is to evaluate collaboration strategy and principles during development plan periods and investigate cooperative resource mobilization. Secondary data and descriptive statistics are used to analyze tables, pie charts, and line graphs. A simple regression model considers employment and debt investment as two variables. Regression analysis reveals that debt investment positively impacts employment during the study period. Every additional unit of debt investment results in a 1.12 percent increase in employment. The results imply that debt investment and employment significantlyimpact during the study period.